Effect of acute and chronic xenon inhalation on erythropoietin, hematological parameters, and athletic performance - Dias, K. A.; Lawley, J. S.; Gatterer, H.; Howden, E. J.; Sarma, S.; Cornwell 3rd, W. K.; Hearon Jr., C. M.; Samels, M.; Everding, B.; Liang, A. S. W.; Hendrix, M.; Piper, T.; et al. (Journal of Applied Physiology, 2019)
This study aimed to assess the efficacy of acute subanesthetic dosages of xenon inhalation to cause erythropoiesis and determine the effect of chronic xenon dosing on hematological parameters and athletic performance. To assess the acute effects, seven subjects breathed three subanesthetic concentrations of xenon: 30% fraction of inspired xenon (FiXe) for 20 min, 50% FiXe for 5 min, and 70% FiXe for 2 min. Erythropoietin (EPO) was measured at baseline, during, and after xenon inhalation. To determine the chronic effects, eight subjects breathed 70% FiXe for 2 min on 7 consecutive days, and EPO, total blood, and plasma volume were measured. Phase II involved assessment of 12 subjects for EPO, total blood volume, maximal oxygen uptake, and 3-km time before and after random assignment to 4 wk of xenon or sham gas inhalation. FiXe 50% and 70% stimulated an increase in EPO at 6 h [+2.3 mIU/mL; 95% confidence interval (CI) 0.1-4.5; P = 0.038] and at 192 h postinhalation (+2.9 mIU/mL; 95% CI 0.6-5.1; P = 0.017), respectively. Seven consecutive days of dosing significantly elevated plasma volume (+491 mL; 95% CI 194-789; P = 0.002). Phase II showed no significant effect on EPO, hemoglobin mass, plasma volume, maximal oxygen uptake, or 3-km time. Acute exposure to subanesthetic doses of xenon caused a consistent increase in EPO, and 7 consecutive days of xenon inhalation significantly expanded plasma volume. However, this physiological response appeared to be transient, and 4 wk of xenon inhalation did not stimulate increases in plasma volume or erythropoiesis, leaving cardiorespiratory fitness and athletic performance unchanged. NEW & NOTEWORTHY This is the first study to examine each element of the cascade by which xenon inhalation is purported to take effect, starting with measurement of the hypoxia-inducible factor effector, erythropoietin, to hemoglobin mass and blood volume and athletic performance. We found that acute exposure to xenon increased serum erythropoietin concentration, although major markers of erythropoiesis remained unchanged. While daily dosing significantly expanded plasma volume, no physiological or performance benefits were apparent following 4 wk of dosing.